Upaya Kepala Sekolah Dalam Meningkatkan Pendekatan Multibudaya di Sekolah Dasar Negri Pasirsari 01 - Shabrina, Hadifah Nur; Umar, Abu Bakar; Waluyo, Kasja Eki (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This study aims to identify and analyze the efforts made by the principal in improving the multicultural learning approach at Pasirsari 01 Elementary School. This study uses a descriptive qualitative method to reveal the efforts of the Principal of Pasirsari 01 Elementary School, Mr. Wanto, S.Pd, in improving the multicultural approach at school. Data were obtained through interviews, observations, and documentation, with the main data source coming from the words and actions of the respondents who were observed. The analysis technique involves collecting, reducing, presenting, and concluding relevant data from the field. The results of this work are The implementation of multicultural education at Pasirsari 01 Elementary School has succeeded in creating an inclusive learning environment and respecting cultural differences among students. With strategies that involve integrating cultural values ​​into the curriculum and daily activities, as well as good communication and cooperation between the principal and teachers, multicultural education has increased students' awareness of the importance of respecting differences and forming a strong attitude of tolerance.